The Forefront for Novel Therapeutic Agents Based on the Pathophysiology of Lower Urinary Tract Dysfunction: α-Blockers in the Treatment of Male Voiding Dysfunction - How Do They Work and Why Do They Differ in Tolerability? - Martin C. Michel (Elsevier, 2010)
α1-Adrenoceptor antagonists are the mainstay of medical treatment of male voiding dysfunction which typically is attributed to benign prostatic hyperplasia. While original concepts have assumed that they relieve voiding dysfunction by relaxing prostatic smooth muscle, newer data indicate that their therapeutic effects at least partly occur independent of prostatic relaxation, perhaps involving direct effects on blood vessels, urothelium, afferent nerves, and/or smooth muscle of the urinary bladder. The adverse event profiles differ among α1-adrenoceptor antagonists, with tamsulosin having a particularly good cardiovascular tolerability. While this was originally attributed to its selectivity for α1A-adrenoceptors, it appears that alfuzosin which lacks subtype-selectivity, has a very similar tolerability. In contrast, doxazosin and terazosin, which are chemically and pharmacologically more closely related to alfuzosin than to tamsulosin, appear to have more side effects attributable to the cardiovascular system. More recent data indicate that tolerability differences between α1-adrenoceptor antagonists may at least partly relate to pharmacokinetic rather than to pharmacodynamic differences. Taken together, these data emphasize the idea that concepts about drug efficacy and tolerability despite being highly plausible may not necessarily be true and always require thorough experimental testing. Keywords:: benign prostatic hyperplasia, alfuzosin, doxazosin, tamsulosin, terazosin, lower urinary tract